Prevalence of Transmitted HIV drug resistance in antiretroviral treatment naïve newly diagnosed individuals in China - Zhao, Shuai (Sci Rep, 2018)
To investigate the prevalence and temporal trend of transmitted drug resistance (TDR), a nationwide cross-sectional survey was conducted among 5627 ART naïve newly diagnosed HIV-infected individuals in 2015 in China. Totally 4704 partial pol sequences were obtained. Among them, the most common HIV-1 circulating recombinant form (CRF) or subtype was CRF01_AE (39.0%), followed by CRF07_BC (35.6%), CRF08_BC (8.9%), and subtype B (5.5%). TDR mutations were found in 3.6% of the cases, with 1.1% harboring TDR to protease inhibitors (PIs), 1.3% having TDR to nucleoside reverse transcriptase inhibitors (NRTIs), and 1.6% to non-nucleoside reverse transcriptase inhibitors (NNRTIs). No significant difference was found in the prevalence of TDR, as compared with the results of another nationwide survey performed among ART naïve HIV-infected people in between 2004 and 2005, except in the 16–25 year-old group. In addition, four drug-resistant transmission clusters were identified in phylogenetic trees, accounting for 6.2% (9/145) of the individuals with TDR. Although the rate of TDR remained relatively low in the past 10 years in China, surveillance is still needed to monitor the trend of TDR and to optimize the first-line regimens.